2013
DOI: 10.5194/acp-13-7473-2013
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal cycle and modal structure of particle number size distribution at Dome C, Antarctica

Abstract: We studied new particle formation and modal behavior of ultrafine aerosol particles on the high East Antarctic plateau at the Concordia station, Dome C (75°06' S, 123°23' E). Aerosol particle number size distributions were measured in the size range 10–600 nm from 14 December 2007 to 7 November 2009. We used an automatic algorithm for fitting up to three modes to the size distribution data. The total particle number concentration was low with the median of 109 cm−3. There was a clear seasonal cycle … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
70
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 53 publications
19
70
0
Order By: Relevance
“…3e). This NPF event was associated with winds from the contaminated sector (10-90 • ) and possibly affected by the diesel generator of the station and motor vehicle pathways (Järvinen et al, 2013). These NPF events occurred after sunrise between about 00:00 and 06:00 UTC (between 08:00 and 14:00 in the local UTC + 8:00 time zone), which is in line with the proposed importance of photochemistry in NPF events and particle growths (Kulmala and Kerminen, 2008;Ehn et al, 2014;Kulmala et al, 2014).…”
Section: Npf Eventssupporting
confidence: 62%
See 3 more Smart Citations
“…3e). This NPF event was associated with winds from the contaminated sector (10-90 • ) and possibly affected by the diesel generator of the station and motor vehicle pathways (Järvinen et al, 2013). These NPF events occurred after sunrise between about 00:00 and 06:00 UTC (between 08:00 and 14:00 in the local UTC + 8:00 time zone), which is in line with the proposed importance of photochemistry in NPF events and particle growths (Kulmala and Kerminen, 2008;Ehn et al, 2014;Kulmala et al, 2014).…”
Section: Npf Eventssupporting
confidence: 62%
“…and a minimum distance of 1100 km from the coastline (Becagli et al, 2012). Measurements were taken at the same sampling site used by Järvinen et al (2013) and Becagli et al (2012), located upwind in the direction of the prevailing wind at a distance of about 1 km southwest of the main station buildings. The northeastern direction is therefore considered as the contaminated sector (10-90 • ), due to local emissions from diesel generators and motor vehicles.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have previously observed enhanced aerosol number concentrations in the AFT (e.g. Ito et al, 1986;Osada et al, 2006;Hara et al, 2011b), and even more have suggested it as the dominant source region of Antarctic aerosol (Ito, 1989(Ito, , 1993(Ito, , 1995Virkkula et al, 2009;Asmi et al, 2010;Järvinen et al, 2013;Koponen et al, 2003). We speculate that the absence of signs of growth in the data presented in this study could be a result of condensational growth halting, possibly due to exhaustion of the precursor source, prior to reaching the measurement location.…”
Section: Air-mass Historymentioning
confidence: 99%